2008
DOI: 10.1007/s11661-008-9522-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fatigue-Crack Surface Crystallography for Al-Zn-Cu-Mg-Mn/Zr

Abstract: The scanning electron microscope (SEM)-based electron backscattered diffraction (EBSD)/ stereology technique quantitatively establishes distributions of the crystallographic characteristics of environmental-fatigue crack features for slightly overaged Al-Zn-Cu-Mg-X (X = Zr or Mn) alloys stressed in the low-growth-rate regime. Results for these homogeneous slip alloys conform to a substantial companion study of planar slip-prone Al-Cu-Mg/Li. Transgranular-crack characteristics are similar for the Mn and Zr vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 58 publications
(133 reference statements)
2
15
0
Order By: Relevance
“…9, crack nucleation occurred toward the center of a grain on a near-{0 0 1} crystallographic plane with the crack-surface normal inclined 28°from the global loading direction. The observed crack nucleation on a near-{0 0 1} plane rather than a {1 1 1}-slip plane seems to be consistent with observations of environmental hydrogenassisted fatigue cracking [9,[15][16][17]57], though the precise mechanism cannot be substantiated from the current study.…”
Section: Discussion Of Results From Al-mg-si Specimensupporting
confidence: 85%
See 3 more Smart Citations
“…9, crack nucleation occurred toward the center of a grain on a near-{0 0 1} crystallographic plane with the crack-surface normal inclined 28°from the global loading direction. The observed crack nucleation on a near-{0 0 1} plane rather than a {1 1 1}-slip plane seems to be consistent with observations of environmental hydrogenassisted fatigue cracking [9,[15][16][17]57], though the precise mechanism cannot be substantiated from the current study.…”
Section: Discussion Of Results From Al-mg-si Specimensupporting
confidence: 85%
“…For many aluminum alloys under certain conditions, crack nucleation and early propagation have been associated with a {1 1 1} slip-based mechanism identified as Stage I cracking [52][53][54][55][56]. Alternatively, a number of studies have revealed non-slip-based mechanisms in aluminum alloys, often with crack paths near parallel to {0 0 1}, {1 0 1}, or high-index planes [9,[15][16][17]57]. These non-slipbased observations have been attributed to environmental hydrogen-assisted cracking.…”
Section: Discussion Of Results From Al-mg-si Specimenmentioning
confidence: 99%
See 2 more Smart Citations
“…SEM fractography of UHV K-shed fracture surfaces ( Figure 8) for both T-L and L-T oriented specimens demonstrate faceted features (Figure 8a and 8c, respectively) at low ΔK. Prior work on this lot of material [61] and other precipitation hardened Al alloys [62,63] cracked in inert environments used quantitative crack-surface stereology coupled with EBSD to establish that such facets are characteristic of slip band cracking (SBC) parallel to {111} slip planes. Consistent with prior work, this SBC morphology is not observed at higher ΔK ( Figure 8b and 8d), likely due to elimination of discretely localized planar slip banding through activation of multiple slip systems as the stress intensity range and crack tip plasticity increase.…”
Section: Fracture Surface Morphologymentioning
confidence: 99%